Ground motion prediction equations for Pacific earthquakes developed by method of correlation - Sanchez, Arvin D.
Ground motion prediction equations (GMPEs) are analytical expressions describing the dependence of ground motion parameters with source, path, and site paranleters. The source can be modeled by using earthquake magnitude and fault characteristics. The path is characterized by using distances reckoned from the tectonic origin to the recording medium. Site parameters describe the type of underlying strata to account for possible amplification effects. This study intends to develop ground motion models for estimating future earthquakes occurring within the Circum-Pacific Belt. The equations as outputs of this study are assessed base on their appropriateness as prediction equations. Strong motion data in the form of digitized acelerograms were collected from different databanks whether received by hand or downloaded on the Worldwide Web. Upon completion of the data gathering phase, there are about 37 different earthquake events in the Pacific Region collected. After applying all the restrictive criteria the remaining data include 140 accelerometric recordings. Upon extraction of the ground motion parameters from each accelerogram, an equation discovery approach for coming up with the final regression relation is performed. The first assumption is an all-linear model for the predictors and the response parameter. Next, all responses are transformed to their corresponding logarithms and linear regression is performed. Lastly, non-linear models relating the transformed responses were declared as the final form of the regression model. To assess the adequacy of the final models, statistical parameters such as model bias and standard error were interpreted. The ground motion models starting trom the attenuation relationship of peak horizontal acceleration (PHA) to the frequency content GMPE have standard deviations of 0.2487, 0.4209, and 1.0229 respectively. Also, the model biases corresponding to the same order of the GMPEs are 2.6718, -0.3772, and -5.4276. From the qualitative and quantitative measures of estimation adequacy, all three models do not meet the criteria for being a GMPE. Since the assumptions made for the residuals are satisfied for the final models, the assumed form for each model is therefore adequate.